LITERATURE TEACHING IN THE EDUCATION UNIT LEVEL CURRICULUM (KTSP) AND CURRICULUM 2013 (K13) AT HIGH SCHOOL LEVEL IN THE DIGITAL ERA (PENGAJARAN SASTRA DALAM KTSP DAN K13 JENJANG SMA DI ERA DIGITAL) - Triono, Eko; Suwandi, Sarwiji; Andayani, Andayani (Universitas PGRI Sumatera Barat, 2019)
Literature learning in Industrial Revolution 4.0 era must be adaptive to the development of internet-based media. The emergence of social media helped facilitate the expression and appreciation of high school students' literature. The formal education curriculum in high school should have responded to developments in the millennium. This research analyzes the objectives, functions, and teaching material of literature in the Education Unit Level Curriculum (KTSP) and Curriculum 2013 (K13) at high school level in the digital era. The study was conducted in a qualitative descriptive. Data is obtained through content analysis and structured interviews. Data analysis is interactively. The results of the study show that the objectives, functions, and teaching material of literature in the 2013 KTSP and Curriculum have not optimally responded to the development of digital literature era.